Behaviour of Biosurfactant Iturin A at Liquid-Liquid Interface - Yadav, Arpita; Bhai Patel, Praveen; Bhaskar, Dhruv; Banerjee, Antara; Sachan, Sadhana (Asian Journal of Chemistry, 2014)
ab initio molecular orbital calculations combined with molecular dynamics simulations have been performed on biosurfactant Iturin A. Intermolecular interaction results indicate that self aggregation of Iturin A is thermodynamically favored even in gas phase. In presence of a medium it will be further facilitated. Inverted micellar formation is predicted to be a spontaneous process and must occur at oil-water interface keeping polar heads towards water surface. Elucidation of this mode of action will complement research in designing pepfactants with synthetic ease and industrial applications. Biosurfactants are widely used in membrane stabilization studies and biotechnology experiments. Simulations carried out in this study indicate that these compounds can be used to enhance delivery of nuclear targeted drugs, in particular as anticancer agents, because they form a polar core and outer hydrophobic surface when self aggregating at lipid interface.